The effects of traditional Chinese exercises on anxiety and depression in adults: a systematic review and network meta-analysis - Huan Feng; YanJing Li; QingChuan Wang; Ye Tao; ZhiHua Wang (Frontiers in Public Health)
ObjectiveTo systematically evaluate the comparative effectiveness of traditional Chinese exercises (TCEs) and other interventions for managing anxiety and depression in adults using a network meta-analysis approach.DesignSystematic review and network meta-analysis.MethodsLiterature search was conducted in Embase, PubMed, Web of Science, and Cochrane Library from inception to December 31, 2024. Randomized controlled trials (RCTs) involving TCEs for adults with anxiety or depression were included. Two reviewers independently screened studies, extracted data, and assessed risk of bias using the ROB2 tool. Bayesian network meta-analyses were performed to compare the effectiveness of interventions. The surface under the cumulative ranking area (SUCRA) was used to rank the interventions.Data sourcesEmbase, PubMed, Web of Science, and Cochrane Library.Eligibility criteria for selecting studiesRCTs involving adults aged 18 years and older, intervention groups engaging in TCEs, comparator groups with no intervention, routine treatment, or distinct interventions, reported outcomes related to anxiety or depression assessed using validated tools, and studies published in English or Chinese.ResultsA total of 82 RCTs were included, with 4,501 participants. For anxiety, Liu Zi Jue (SUCRA = 99.5%), Tai Chi (SUCRA = 87.6%), and CBT (SUCRA = 75.3%) were the most effective interventions. For depression, Tai Chi (SUCRA = 95.5%), Yijinjing (SUCRA = 89.2%), and CBT (SUCRA = 83.6%) ranked as the most effective. TCEs demonstrated comparable or superior efficacy to well-established interventions like CBT. The study also found that TCEs have high adherence rates, low costs, and the potential for large-scale promotion and value.ConclusionThis systematic review and network meta-analysis provides evidence for the efficacy of TCEs, particularly Tai Chi, Liu Zi Jue, and Yijinjing, in managing anxiety and depression in adults. Despite limitations such as heterogeneity in intervention protocols and study populations, the findings suggest that these exercises offer therapeutic benefits and may serve as accessible, cost-effective, and culturally-relevant treatment options. Further research is needed to establish optimal dosages, assess long-term effects, and evaluate generalizability across diverse contexts.Systematic review registrationCRD42025637146.